Understanding Pro-Environmental Behavior in the Hospitality Industry: A Systematic Review of Employee and Consumer Perspectives - Jayanti, Lilis; Wulandari, Wisi (Politeknik Negeri Bandung, 2025)
Purpose – This study systematically reviews and synthesizes the literature on pro-environmental behavior (PEB) in the hospitality industry, integrating both employee and consumer perspectives. It aims to identify dominant theoretical frameworks, methodological trends, and contextual gaps shaping sustainability-oriented behavior research in hospitality. Design/methodology/approach – A systematic literature review (SLR) was conducted in accordance with PRISMA 2020 guidelines. A total of 29 peer-reviewed articles published between 2019 and 2025 were retrieved from Scopus-indexed journals and analyzed using qualitative thematic coding complemented by bibliometric mapping to identify publication trends, theoretical dominance, and regional distribution. Findings – The results indicate that PEB research in hospitality is heavily grounded in cognitive–normative models, particularly the Theory of Planned Behavior and Value–Belief–Norm theory, which together account for the majority of empirical studies. Most research adopts cross-sectional, survey-based designs, with growing but still limited use of experimental and mixed-method approaches. Empirically, PEB is driven by cognitive, normative, and affective antecedents, while organizational enablers—such as green human resource management, ethical climate, and marketing authenticity—play a critical mediating role. The literature remains geographically concentrated in Asia and Europe and continues to rely predominantly on self-reported behavioral measures. Originality/value – By adopting a dual-actor perspective, this review advances the hospitality sustainability literature by integrating fragmented employee- and consumer-focused research into a coherent analytical framework. The study contributes theoretically by highlighting the limitations of dominant rationalist models and identifying pathways for integrating behavioral, organizational, and emotional perspectives, while methodologically outlining directions for more robust, field-based, and cross-contextual research.